PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE PADA MAHASISWA POLITEKNIK NEGERI UJUNG PANDANG - Rais Akbar; Syahriah Sari; Jayadi Jayadi (Journal of Business Administration (JBA), 2023)
This study aims to determine (1) To determine the quality of Smartphone Iphone products on students at the State Polytechnic of Ujung Pandang. (2) To determine the brand image of Smartphone Iphone on students of the State Polytechnic of Ujung Pandang. (3) To find out the decision to purchase Smartphone Iphone on students of the State Polytechnic of Ujung Pandang. (4) To find out the quality of the product has a partial effect on the decision to purchase Smartphone Iphone. (5) To find out the quality of the product has a partial effect on the decision to purchase Smartphone Iphone. (6) To find out the product quality and brand image have a simultaneous effect on the purchasing decision of Smartphone Iphone. The research population is Smartphone Iphone users at the Ujung Pandang State Polytechnic students. The results of this study are: (1) Product quality has a positive and significant effect on purchasing decisions with a regression value of 0.286 and the results of the t test where the t count value of 6.158 is greater than the t table value of 1.98447 and the significant level is less than 0 .05 which is 0.00. (2) Brand image has a positive and significant effect on purchasing decisions with a regression value of 0.085 and a significance level of 0.000. (3) Product Quality and Brand Image simultaneously have a positive and significant effect on purchasing decisions with a significance level of 0.000 less than 0.05 (p<0.05), and the adjusted R2 of Product Quality and Brand Image on Purchase Decisions is 3.050 . The limitation of this research is only the students of the State Polytechnic of Ujung Pandang. Keywords: Product Quality and Brand Image and Purchase Decision. Â